The Correlation of Value Chain, Service Quality, and Web Quality on Consumer Satisfaction - Mirza Abdi Khairusy; Ratih Hurriyati; Puspo Dewi Dirgantari; Yogi Suprayogi (Jurnal Ad'ministrare, 2021)
The development of online shopping platforms is increasing day by day. This is evidenced by the number of online stores. Shopee is one of the commercial online sites in Indonesia with various attractive offers to its consumers, both in the form of discounts on expedition fees to discounts on food prices. This phenomenon attracted the attention of researchers to find out how much influence Value Chain, Service Quality and Web Quality had on Customer Satisfaction on the Shopee application at Sultan Ageng Tirtayasa University. This type of research uses a quantitative approach. The sample in this study was 170 consumer respondents and used multiple linear regression. These results are obtained that the hypothesis of the three variables can be accepted. In addition, this study can also provide excellent input for the development of the Shopee application business. The limitations of the study are that the respondents obtained as many as 170 and were conducted at the University of Sultan Ageng Tirtayasa. It is recommended that further research increase the significance of sampling by expanding the sample size and conducting surveys in a wider geographic area.